Training and nutritional practices of triathletes competing in the 1998 Noosa Triathlon - Abt, G. A.; Mummery, W. K.; Coutts, A. J.; Reaburn, P. R.; Dickson, G.; Rowsell, G.; Schofield, G. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Triathlon is a relatively new sport that has recently been accepted as an Olympic sport for Sydney 2000. While the training and nutritional practices of elite and non-elite Ironman (long distance) triathletes has been well documented, little empirical research has examined these practices in the more popular Olympic Distance Triathlon (ODT) held over a 1.5 km swim, 40 km bicycle and 10km run. The aim of the present study was to retrospectively obtain information regarding the training and nutritional practices of triathletes competing in the 1998 Noosa ODT. A self-reporting questionnaire addressing demographics and both training and nutritional practices was completed by 210 volunteer athletes. Participant characteristics for gender, age, body mass, height and category were male 75%, female 25%, 33 ± 9 years, 73 ± 13 kg, 176 ± 8 cm, 90% individual and 10% team, respectively. A selection of results is displayed in Table 1. The results suggest that ODT triathletes' training volumes reflect the time demands of the actual ODT race. Additionally, it would appear that triathletes are convinced of the benefits of carbohydrate drinks and multivitamin supplementation as aids to ODT performance. However, the use of ergogenic aids such as creatine monohydrate and sodium bicarbonate that may not play a role in endurance performance need addressing through public education.